Pengaruh Gaya Kepemimpinan dan Kompensasi terhadap Kepuasan Kerja Karyawan PT. Victory Internasional Futures Cabang Kota Malang - Fatahillah DN; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to see the effect of leadership style and compensation on job satisfaction of employees of Pt. Victory International Futures Malang City Branch. The variables used in this study are Job Satisfaction as the dependent variable, while the independent variables are Leadership Style and Compensation. Respondent data collection was carried out through a questionnaire method with a sample size of 67 respondents.The results of this study simultaneously conclude that there is an influence between the variable leadership style and compensation on job satisfaction with commitment and partially conclude that there is an influence between leadership style and compensation on job satisfaction on commitment.Keywords: Leadership Style, Compensation, Job Satisfaction